PENGARUH PENGGUNAAN CELEBRITY ENDORSER PADA MEDIA SOSIAL INSTAGRAM TERHADAP MINAT BELI KONSUMEN (Studi Pada Mahasiswa Program Studi Administrasi Bisnis Universitas Mulawarman Angkatan 2015-2016) - Wahyuni Wahyuni (Jurnal Administrasi Bisnis Fisipol Unmul, 2020)
This study to purposed to examine the effect of attractive, trustworthiness, expertise by the celebrity endorser on social media instagram simultaneously, partial and dominant towards consumers’ purchase interest.The variable that used in this study consists of independent variables, those are atteractive (X1), trustworthinees (X2), and expertise (X3) also dependent variable, purchase interest (Y). This study is using quantitative research method counted 119 consuners and using nonpropability sampling. Interview, questionnaire, and observation are using to collect the data. The data analysis using multiple linear technique.Based on the result of the research, test F (simultaneous) and test t (partial) showed that atteractive variable, trustworthiness, and expertise simultaneously and partial significantly influent the consumers’ purchase interest, the biggest standardised coefficients beta is atteractive, so that we can conclude that the most influent variable is atterctive variable (X1). For all online businesses, especially instagram, it is better to pay attention in chosing the celebrity that worthy to be tha endorser so that we can get the terustworthiness and antention from the consumers and to influence the consumers’ perception to do a pruchase.